An Estimation of Expenditures, Own and Cross Price Elasticities of Milk in Pakistan - Irfan Ullah, Akram Ali, Waheed Ullah, Akhtar Ali, Muhammad Suhail, Ijlal Haider, Iqra Babar (International Journal of Modern Agriculture, 2021)
In the last few decades more attention is given to consumer demand analysis in the country as well as worldwide. The rise in the prices of food commodities in Pakistan improved the researcher concentration in the pragmatic study of consumer demand analysis. The income and price demand elasticities are of paramount importance in understanding the consumers’ behaviour of the country. Working lesser model is used to evaluate the household’s demand, expenditures, own and cross-price elasticities for milk and its product in rural and urban regions of Pakistan in this study. For this purpose, Household’s Integrated Economics Survey (HIES) cross sectional data for the year 2013-14 with a sample size of 17989 was used. The results revealed that rural households spend more income on food items as compared to urban households. The estimated expenditure elasticities of selected milk products in both the regions were inelastic except other milk products in rural region.The own price elasticities for all selected milk products were negative and price inelastic except milk fresh in both the regions, milk pack in rural region. while, yoghurt in both the regions were price elastic. All the cross-price elasticities of milk products were negative and less than unity which reveals that these products are compliments.Based on the findings of this research study it is recommended that any increase in the prices of fresh milk and yoghurt will result significant decrease in their consumption and for food insecure household’s government should supply fresh milk and processed form in subsidizing prices in utility stores.